PENGOLAHAN RUMPUT LAUT Turbinaria murayana SEBAGAI PAKAN ALTERNATIF AYAM KUB PADA KELOMPOK TERNAK SERUMPUN SUNGAI NIPAH KABUPATEN PESISIR SELATAN - Reski, Sepri; Mahata, Maria Endo; Rizal, Yose; Rusli, Ridho Kurniawan; Firdani, Fea; Aritama, Iqbal; Putri, Jihan Nabila; Cristina, Dina; Noorsa, Dion; Suardi, Muhammad Fauzan (Jurnal Hilirisasi IPTEKS, 2025)
This program was implemented in the Serumpun Livestock Group at Sungai Nipah Beach, Pesisir Selatan Regency, West Sumatra Province. The activity aimed to introduce the processing method of brown seaweed (Turbinaria murayana) before its incorporation into the diet of the Kampung Unggul Balitbangtan chicken (KUB). The methods employed included educational outreach, demonstrations, and hands-on training sessions. The outreach component covered the potential of Turbinaria murayana as an alternative feed ingredient and the processing stages from harvesting to ready-to-use feed. The training sessions demonstrated processing techniques, including freshwater soaking, sun-drying, and mechanical grinding. This activity was attended by 20 participants from the livestock group, consisting of 15 women and five men. The results showed an 85% improvement in participants' knowledge and skills in utilizing and processing Turbinaria murayana as a feed ingredient for KUB chickens. Farmers gained a better understanding of the nutritional content and potential of Turbinaria murayana, as well as effective processing methods to optimize its use in feed formulations. In conclusion, the program successfully enhanced farmers' understanding and practical skills in utilizing Turbinaria murayana seaweed as a feed ingredient for KUB chickens. It also reduced feed costs and supported the development of poultry feeds that were more economical than conventional ingredients such as ground corn, rice bran, and fish meal.